Analysis of e-mentoring platform for future leaders’ development - Mohamad Nur Salam Man; Halimah Abdul Manaf (Penerbit Universiti Kebangsaan Malaysia, 2023)
Future leaders need to be developed via a variety of techniques. Some government agencies or corporate companies have established and implemented a conventional mentoring programme to prepare a future leader for top-level management. A mentoring programme may increase productivity and occupational satisfaction based on the most recent research. Over time, it can result in the proteges of future leaders. Strong interactions among the mentor and the protege are characteristic of mentoring. Recently, a mentor and protege mutual connection via modern technology-mediated simultaneous learning has emerged as the current strategy for advancing virtual teams and leadership development inside the organisation. By analysing some of the tools, criteria, approaches, and processes of the mentoring platform using technology used by some organisations today in developing an effective future leader, this conceptual paper intends to establish a significant analysis of the review of related literature research on the subject. It does this through a technology-mediated approach and a new resilient and competitive leadership development management.